2014
DOI: 10.1016/j.ijpara.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hc-daf-2 encodes an insulin-like receptor kinase in the barber’s pole worm, Haemonchus contortus, and restores partial dauer regulation

Abstract: Infective L3s (iL3s) of parasitic nematodes share common behavioural, morphological and developmental characteristics with the developmentally arrested (dauer) larvae of the free-living nematode Caenorhabditis elegans. It is proposed that similar molecular mechanisms regulate entry into or exit from the dauer stage in C. elegans, and the transition from free-living to parasitic forms of parasitic nematodes. In C elegans, one of the key factors regulating the dauer transition is the insulin-like receptor (desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 98 publications
4
32
0
Order By: Relevance
“…PI3Ks, which are relatively conserved enzymes from unicellular eukaryotes to multicellular organisms, play important roles in intracellular trafficking, cell metabolism, differentiation and/or survival [53][54][55][56]. Recently, components of insulinlike signalling have been identified in parasitic nematodes, including A. caninum [37,38], H. contortus [39,40] and S. stercoralis [30,41,42,57], suggesting that similar signalling is utilized by both free-living and parasitic nematodes. In the present study, two PI3K genes were identified in H. contortus using available data [33], including a Hc-age-1 encoding a p110 catalytic subunit and a Hc-aap-1 encoding a p50/p55-like regulatory subunit, consistent with those in C. elegans and S. stercoralis [12,13,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PI3Ks, which are relatively conserved enzymes from unicellular eukaryotes to multicellular organisms, play important roles in intracellular trafficking, cell metabolism, differentiation and/or survival [53][54][55][56]. Recently, components of insulinlike signalling have been identified in parasitic nematodes, including A. caninum [37,38], H. contortus [39,40] and S. stercoralis [30,41,42,57], suggesting that similar signalling is utilized by both free-living and parasitic nematodes. In the present study, two PI3K genes were identified in H. contortus using available data [33], including a Hc-age-1 encoding a p110 catalytic subunit and a Hc-aap-1 encoding a p50/p55-like regulatory subunit, consistent with those in C. elegans and S. stercoralis [12,13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous complementation showed that the main components of insulin-like signalling, including daf-16, daf-2, age-1 and daf-12 in parasitic nematodes [37,[39][40][41]67], have similar functions to C. elegans orthologues. However, it is, nonetheless, interesting to note that the roles of PI3K from H. contortus appear to be divergent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a number of groups, including us, have reported the successful expression of proteins from parasitic nematodes in C. elegans [18]. However, most, if not all, of these proteins are active as either monomers or homomeric multimers.…”
Section: Introductionmentioning
confidence: 99%